Changing Beliefs about Trauma: A Qualitative Study of Cognitive Processing Therapy. Issue 2 (16th December 2014) - Price, Jennifer L.; MacDonald, Helen Z.; Adair, Kathryn C.; Koerner, Naomi; Monson, Candice M.
Abstract : Background: Controlled qualitative methods complement quantitative treatment outcome research and enable a more thorough understanding of the effects of therapy and the suspected mechanisms of action.Aims: Thematic analyses were used to examine outcomes of cognitive processing therapy (CPT) for posttraumatic stress disorder (PTSD) in a randomized controlled trial of individuals diagnosed with military-related PTSD ( n = 15).Method: After sessions 1 and 11, participants wrote "impact statements" describing their appraisals of their trauma and beliefs potentially impacted by traumatic events. Trained raters coded each of these statements using a thematic coding scheme.Results: An analysis of thematic coding revealed positive changes over the course of therapy in participants' perspective on their trauma and their future, supporting the purported mechanisms of CPT.Conclusion: Implications of this research for theory and clinical practice are discussed.